Chiral Recognition R- and RS- of New Antifungal: Complexation/Solubilization/Dissolution Thermodynamics and Permeability Assay - Tatyana V. Volkova; Olga R. Simonova; Igor B. Levshin; German L. Perlovich (MDPI AG, 2022)
Novel potential antifungal of 1,2,4-triazole class have been synthesized as pure enantiomer (R-98) and racemic (RS-186). The effect of 2-hydroxypropyl-β-cyclodextrin (CD) on the solubility and permeability of RS-186 and R-98 in terms of chiral recognition was investigated. Phase solubility studies were carried out at 4 temperatures in 0-0.05 M CD concentration range for pH 2.0 and pH 7.4. <semantics>AL</semantics>- and <semantics><msubsup>AL−</msubsup></semantics>-type phase-solubility profiles were obtained for both compounds in pH 2.0 and pH 7.4. The racemic formed more stable complexes with CD as compared to R-isomer. Disclosing of chiral discrimination was facilitated using the approach based on the complex consideration of the derived complexation/solubilization/inherent dissolution thermodynamic functions, including the differential parameters between the racemic compound and R-enantiomer. The differences in the thermodynamic parameters determined by the chirality were discussed in terms of the driving forces of the processes and the main interactions of the compounds with CD in solution. The membrane permeability of both samples in the presence of CD was accessed in order to evaluate the specificity of enantioselective transport through the lipophilic membrane. The solubility/permeability interrelation was disclosed. The investigated compounds were classified as medium permeable in pure buffers and low permeable in the presence of 0.01 M CD. The obtained results can be useful for the design of pharmaceutical products in the form of liquid formulations based on the investigated substances.